Citizens in motion : emigration, immigration, and re-migration across China's borders - Ho, Elaine Lynn-Ee (Stanford University Press, 2019)
'Citizens in Motion' argues that analyzing emigration, immigration and re-migration under the framework of contemporaneous migration directs attention to the citizenship formations that are forged across migration sites, shaping the lives of citizens in motion.